Emergence, Downward Causation, and Interlevel Integrative Explanations - Santos, Gil (2023)
In this article, I propose a unified account of systemic emergence, downward causation, and interlevel integrative explanations. First, I argue for a relational-transformational notion of emergence and a structural-relational account of downward causation in terms of both its transformational and conditioning effects. In my view, downward causation can avoid the problems traditionally attributed to it, provided that we are able to reconceptualize the notion of ‘whole’ and that form of causality in a purely relational way. In this regard, I distinguish contextual or whole-to-part causation from downward causation, the latter defined by the existence of second-order structural relations. Finally, I argue that while emergence and downward-structural causation imply the in-principle failure of micro-determinism and therefore micro-reduction, they do not rule out the possibility of any type of explanation. On the contrary, they call for the development of interlevel integrative explanations.